2020
DOI: 10.1111/desc.12973
|View full text |Cite
|
Sign up to set email alerts
|

Off to a good start: Early Spanish‐language processing efficiency supports Spanish‐ and English‐language outcomes at 4½ years in sequential bilinguals

Abstract: Many Latino children in the U.S. speak primarily Spanish at home with few opportunities for exposure to English before entering school. For monolingual children, the strongest early predictor of later school success is oral language skill developed before kindergarten. Less is known about how early oral language skills support later learning in sequential bilingual children. A question with wide-reaching significance is whether skill in a child's first language (L1) supports later learning in a second language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…Earlier age of acquisition and longer use typically lead to better language outcomes (Birdsong, 2009;Bosch et al, 2019;though see Xu Rattanasone et al (2016) for different length of acquisition effects due to language typology in preschoolers). Bilingual children's language experience can also vary in terms of amount of language input and use, with both having effects on language development and spoken narrative skills (Hammer et al, 2012;Marchman et al, 2020). Govindarajan and Paradis (2019) found in school-aged children that length of English exposure in school predicted better English narrative skills, but amount of English input (from non-native speakers) and use at home did not predict macrostructure or microstructure abilities in English.…”
Section: Language Experience and Bilingual Narrative Skillsmentioning
confidence: 99%
“…Earlier age of acquisition and longer use typically lead to better language outcomes (Birdsong, 2009;Bosch et al, 2019;though see Xu Rattanasone et al (2016) for different length of acquisition effects due to language typology in preschoolers). Bilingual children's language experience can also vary in terms of amount of language input and use, with both having effects on language development and spoken narrative skills (Hammer et al, 2012;Marchman et al, 2020). Govindarajan and Paradis (2019) found in school-aged children that length of English exposure in school predicted better English narrative skills, but amount of English input (from non-native speakers) and use at home did not predict macrostructure or microstructure abilities in English.…”
Section: Language Experience and Bilingual Narrative Skillsmentioning
confidence: 99%
“…In recent years, direct lab-based assessments, such as the Looking-While-Listening paradigm (LWL; Fernald et al, 2008) and the Computerized Comprehension Task (CCT; Friend & Keplinger, 2003, have been developed to measure decontextualized vocabulary (e.g., Friend et al, 2019;Legacy et al, 2018;Marchman, Bermúdez, Bang & Fernald, 2020;Poulin-Dubois, Bialystok, Blaye, Polonia & Yott, 2012). While the LWL paradigm assesses decontextualized vocabulary by measuring children's visual word processing, the CCT assesses decontextualized vocabulary by measuring haptic word processing (i.e., latency to touch a correct word referent).…”
Section: How Is Decontextualized Vocabulary Measured?mentioning
confidence: 99%
“…It is well established that early decontextualized vocabulary is associated with both concurrent and later language outcomes among bilingual and monolingual children (Friend et al, 2019;Legacy et al, 2018;Marchman et al, 2020;. For example, around two years of age, bilinguals' performance on the CCT is associated with concurrent contextualized vocabulary size, as measured by the MCDI (Friend & Keplinger, 2008;Friend et al, 2018;Legacy et al, 2018;Poulin-Dubois et al, 2012).…”
Section: Decontextualized Vocabulary and Lexical Growthmentioning
confidence: 99%
“…Learning science in Spanish validated students' cultural and linguistic assets and allowed them to strengthen both their everyday and academic languages (Gottlieb & Ernst-Slavit, 2014). These Spanish language and literacy skills, as research has shown (Collier & Thomas, 2017;Marchman et al, 2020;Phillips Galloway et al, 2020), will also transfer to English, which enables bridging between the two languages. Humor in this classroom also contributed to students feeling more comfortable and open to learning.…”
Section: Differences In Si and Dbe Classroomsmentioning
confidence: 99%